Hypothalamic orexins as possible therapeutic agents in threat and spatial memory disorders - Mazur, Filip; Całka, Jarosław (Frontiers in Behavioral Neuroscience, 2023)
Orexin-A and orexin-B, neuropeptides produced exclusively in the lateral hypothalamus, are implicated in various functions, including memory. Their levels are elevated in certain pathological states like PTSD and lowered in other states, e.g., memory deficits. Recent developments have shown the possibilities of using orexins to modulate memory. Their administration can improve the results of test animals in paradigms like PA (Passive Avoidance), CFC (Cued Fear Conditioning), MWM (Morris Water Maze) etc., with differences between the orexin used and the route of drug administration. Blocking orexin receptors in different brain structures produces opposing effects of memory impairments in given paradigms. Therefore, influencing the orexinergic balance of the brain becomes a viable way to ameliorate memory deficits, shift PTSD-induced recall of stressful memories to extinction path or regulate other memory processes.Conception and design of study: F. Mazur